Determination of glass transition temperature for polymers by methods of thermoactivation spectroscopy - Yurov, V. M.; Laurinas, V. C.; Eremin, E. N.; Gyngazova, M. S. (IOP PUBLISHING LTD, DIRAC HOUSE, 2016)
For rapid determination of glass transition temperature for polymers, we propose a method of thermally stimulated luminescence. The experiments were carried for epoxy polymers dyed and undyed with organic dyes. It is shown that glass transition temperature depends on curing temperature and concentration of the dye. The comparison with the thermogravimetric analysis showed coincidence of the results obtained.